THE ROLE OF STUDYING HUMAN ECOLOGY IN THE TRAINING OF FUTURE DOCTORS - A.K.Kurbanov; Z.Z.Yuldasheva (Research Focus International Scientific Journal, 2024)
The study of issues of medical ecology for the formation of the worldview and clinical thinking of a modern doctor seems extremely important. In everyday work, doctors increasingly deal with blurred, vaguely defined clinical conditions of the human body, the formation of which largely depends on various environmental factors. The quality of atmospheric air largely determines the health status of the population and is an active etiological factor in the development of diseases, primarily in children, the elderly, as well as people suffering from chronic diseases of the respiratory system and cardiovascular system.